Stone of tears - Terry Goodkind Keith Parkinson (TOR, 1995)
The veil of the underworld has been torn. And Darken Rahl, from beyond the veil, has begun to summon a sinister power worse than any he has ever wielded before. Armed with the Sword of Truth, Richard Cypher, now becomes Richard Rahl, must learn to control his new found power, or the world will spin into darkness unending. The Sister of Light promise help. While Richard journeys to their forbidden city, his beloved Read mo